ANALISIS PREFERENSI SISWA MELANJUTKAN KE MTS ALFADHLAH KECAMATAN MINAS TAHUN PELAJARAN 2014/2015 - Khairuddin '; Tri Umari Tri Umari; Rosmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to: (a) to analyze the aspects of internal preference factor into students choose MTS, (b) to analyze aspects of preference External factors that a student choose MTS (c) Analyze category of internal factors become preference students choose MTS, (d) Analyze the category of external factors into the preferences of students choosing MTS. The method used in this study is a descriptive study, the technique of saturated samples (total sampling). The results of this study are: (a) Internal factors become dominant preferences of students choosing MTS is because you want to explore the religion of Islam. (b) external factors which become Preferences students choose MTS is located on indicator indicator desire of parents. (c) Category internal factors become the preference of students choosing MTS in middle category. (d) Category external factors into the preferences of students choosing MTS is located on the lower category. Keywords: Preferences